Bonding of Two 8‐Electron Superatom Clusters. (21st November 2018) - Jin, Shan; Zou, Xuejuan; Xiong, Lin; Du, Wenjun; Wang, Shuxin; Pei, Yong; Zhu, Manzhou
Abstract: We report the observation of dimerization of two 8‐electron superatom cluster units in the crystallographic structures of Au2 Ag42 (SAdm)27 (BPh4 ) and [Au2 Ag48 (S‐ t Bu)20 (Dppm)6 Br11 ]Br(BPh4 )2 nanoclusters. The crystallographic analysis reveals that both nanoclusters have a Au2 Ag24 core made of two separated icosahedral without sharing metal atoms, and each icosahedron has an eight‐electron (8e) closed shell (1S 2 1P 6 ). The valence electronic structures of these two nanoclusters are analogous to that of a Ne atom dimer (Ne2 ) according to the density functional theory (DFT) analysis. This is the first crystallographic observation of the dimerization of 8‐electron superatom units. This study enriches the fundamental knowledge on metal superatom clusters and implies the possibility for further assembling metal superatom building blocks into higher order superatom molecules. Abstract : Dicke Pärchen : Zwei kristallographische Studien zu dimeren 8‐Elektronen‐Überatom‐Clustern – [Au2 Ag42 (SAdm)27 ] + und [Au2 Ag48 (S‐ t Bu)20 (Dppm)6 Br11 ] 3+ – zeigen den Aufbau molekularer Cluster aus Metallüberatomen als Bausteinen und deuten an, dass auch entsprechende Strukturen höherer Ordnung zugänglich sein sollten.